Desenvolvimento de imunossensor eletroquímico para detecção de troponina I: um marcador do infarto agudo do miocárdio - Brussasco, Jéssica Guimarães (2019)
Cardiac biomarkers are molecular species used in clinical practice for the diagnosis or prognosis of diseases, which are released into the bloodstream with the occurrence of a cardiac episode, such as acute myocardial infarction (AMI). Cardiac biomarkers include Troponin I, which is considered the gold standard for early diagnosis of AMI. Since the sensitivity of conventional tests for the early diagnosis of AMI is low and has limitations (such as speed and the need for a skilled workforce), the development of more sensitive analytical methodologies, such as electrochemical immunosensors, is relevant. are versatile platforms, based on highly selective and selective binding between antigens and antibodies. In this work, an electrochemical immunoassay for the detection of troponin I was produced, using graphite electrodes modified with reduced graphene oxide nanocomposite and polythramine, which was able to detect the troponin I biomarker in minute concentrations in serum, whose limit of detection was of the order of 0.2 ng / mL, showed stability of current response within 30 days after its manufacture, ability to reuse by two subsequent analyzes, indicated specificity of response for thetroponin I antigen, besides differentiating (AFM) and scanning electron microscopy (SEM) indicated changes in the surface of the immunosensor, and there was a decrease in the roughness throughout the construction stages, attributed to the formation of the immunocomplex.